Forecasting Imports with Information from Abroad - Christian Grimme; Robert Lehmann; Marvin Noeller (ifo Institute - Leibniz Institute for Economic Research at the University of Munich, 2019)
Globalization has led to huge increases in import volumes, increasing the importance of imports for total output. Since imports are a volatile component, they are difficult to forecast and strongly influence the forecast accuracy of gross domestic product. We introduce the first leading indicator constructed to forecast import growth, the Import Climate. It builds on the idea that the import demand of the domestic country should be reflected in the expected export developments of its main trading partners. A foreign country's expected exports are, in turn, determined by its trading partners' business and consumer confidence and its own price competitiveness. In a real-time forecasting experiment, the Import Climate outperforms standard business cycle indicators at short horizons for France, Germany, Italy, and the United States for the first release of data. For Spain and the United Kingdom, our indicator works particularly well with the latest vintage of data.
Keywords: F01; F10; F17; 330; Import climate; import forecasting; survey data; price competitiveness